Preparation of artificially frozen sand specimens - Baker, T H (Harry) (National Research Council of Canada. Division of Building Research, 1976)
Several specimens of artificially frozen sand (ASTM C-109) were prepared to evaluate different testing procedures and techniques used to determine the mechanical properties of frozen soils. Two methods of preparation of fully saturated frozen sand specimens, described by other investigators, were compared. Compaction by a rodding technique and saturation under vacuum produced a uniform degree of compaction and saturation upon freezing. The most critical part of the preparation procedure leading to physical variability between specimens was found to be the time during freezing and machining. This time span must be kept constant to minimize the effects of sublimation. Plusieurs spécimens de sable géle artificiellement (ASTM C- 109) ont été préparés afin d'évaluer différentes méthodes et techniques d'essai utilisées pour déterminer les propriétés mécaniques de sols gelés. Deux méthodes de préparation de spécimens de sable gelé complètement saturé, décrites par d' autres chercheurs, ont été comparées. Le tassement par une technique de pilonnage et par saturation sous vide a produit un degré uniforme de tassement et de saturation lors de la congélation. La partie la plus critique de la méthode de pré paration pouvant mener à une variabilité physique entre les spécimens a été trouvée comme le temps de congélation et d' ajustage. Cette durée doit être maintenue constante afin de diminuer les effets de la sublimation. Peer reviewed: No NRC publication: Yes